2015
DOI: 10.1007/s11356-015-4749-3
|View full text |Cite
|
Sign up to set email alerts
|

Urinary heavy metals, phthalates, phenols, thiocyanate, parabens, pesticides, polyaromatic hydrocarbons but not arsenic or polyfluorinated compounds are associated with adult oral health: USA NHANES, 2011–2012

Abstract: Links between environmental chemicals and human health have emerged over the last few decades, but the effects on oral health have been less studied. Therefore, it was aimed to study the relationships of different sets of urinary chemical concentrations and adult oral health conditions in a national and population-based setting. Data was retrieved from the United States National Health and Nutrition Examination Surveys, 2011-2012 including demographics, self-reported oral health conditions and urinary environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…It is therefore plausible that the literature on TCS is also affected by publication bias. For example, in performing this review we identified three very similar studies that evaluated the 2011-2012 NHANES data to assess three separate outcomes (oral health, memory problems, and self-reported health status) in relation to urinary levels of heavy metals, phthalates, phenols, thiocyanate, parabens, pesticides, polyaromatic hydrocarbons, and polyfluorinated compounds (Shiue 2015a(Shiue , 2015b(Shiue , 2015c. Although all three analyses were based on the same NHANES data and evaluated the same chemicals, only two papers (Shiue 2015a(Shiue , 2015b included results for TCS, although there were over 500 NHANES participants with both TCS exposure and memory problem data.…”
Section: Consistency Of Methods Results and Reporting Across Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…It is therefore plausible that the literature on TCS is also affected by publication bias. For example, in performing this review we identified three very similar studies that evaluated the 2011-2012 NHANES data to assess three separate outcomes (oral health, memory problems, and self-reported health status) in relation to urinary levels of heavy metals, phthalates, phenols, thiocyanate, parabens, pesticides, polyaromatic hydrocarbons, and polyfluorinated compounds (Shiue 2015a(Shiue , 2015b(Shiue , 2015c. Although all three analyses were based on the same NHANES data and evaluated the same chemicals, only two papers (Shiue 2015a(Shiue , 2015b included results for TCS, although there were over 500 NHANES participants with both TCS exposure and memory problem data.…”
Section: Consistency Of Methods Results and Reporting Across Studiesmentioning
confidence: 99%
“…Of the 43 studies, 24 were conducted in North America (Wolff et al , 2010(Wolff et al , 2015Clayton et al 2011;You et al 2011;Buttke et al 2012;Savage et al 2012Savage et al , 2014Koeppe et al 2013;Lankester et al 2013;Buser et al 2014;Spanier et al 2014;Adgent and Rogan 2015;Li et al 2015;Ihde et al 2015;Shiue 2015aShiue , 2015bVelez et al 2015;Ashley-Martin et al 2016;Buckley et al 2016;Poole et al 2016;Scinicariello and Buser 2016;Smarr et al 2017;Geer et al 2017), two studies in the Caribbean (Watkins et al 2015;Aker et al 2016), 10 studies in Europe (Allmyr et al 2009;Chevrier et al 2012;Philippat et al 2012Philippat et al , 2014Bertelsen et al 2013;Buhl et al 2014;Den Hond et al 2013, 2015Geens et al 2015;Lassen et al 2016), four in Asia (Chen et al 2013;Wang et al 2015;Xue et al 2015;Zhu et al 2016), and three in Australia (Cullinan et al 2012(Cullinan et al , 2015a…”
Section: Overview Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Links between environmental chemicals and human health including self-rated health, hypertension, cardiovascular disease, food allergy, oral health, emotional support, and cognitive function in American adults have emerged in Americans (Shiue 2015a; Shiue 2015b; Shiue 2015c; Shiue 2015d; Shiue 2015e; Shiue 2014; Shiue 2013a; Shiue 2013b; Shiue 2013c), but the effects from polyaromatic hydrocarbons (PAHs) were less studied, compared to other commonly known environmental chemicals such as heavy metals, arsenic, phenols, phthalates, etc. PAHs constitute a group of chemicals that people could be exposed via vehicle exhausts, asphalt, coal tar, wild fires, agricultural burning, soil, charbroiled foods, and tobacco smoke.…”
Section: Introductionmentioning
confidence: 99%